Suppression of airway hyperresponsiveness induced by ovalbumin sensitisation and RSV infection with Y-27632, a Rho kinase inhibitor - Hashimoto, K (BMJ Group, 2002)
Background: Smooth muscle contraction is one of the hallmarks of asthma. A recently developed pyridine derivative, Y-27632, a selective Rho kinase inhibitor, has been reported to inhibit the smooth muscle contraction of human and animal trachea in ex vivo systems but its effect in animal models of airway hyperresponsiveness (AHR) has not been examined. The purpose of this study was to evaluate the effect of Y-27632 in a murine model of allergic and virally induced AHR. Methods: Baseline lung resistance and methacholine induced AHR were measured in mice sensitised to ovalbumin (OVA) and also in mice infected with respiratory syncytial virus (RSV) following ovalbumin sensitisation (OVA/RSV). Results: Time course and dose ranging experiments indicated that 30 mg/kg Y-27632 given by gavage 2 hours before methacholine challenge significantly reduced baseline lung resistance and prevented AHR in OVA sensitised mice. Y-27632 also suppressed AHR induced by the bronchospastic agent serotonin in OVA sensitised mice and prevented methacholine induced AHR in OVA/RSV mice. Conclusions: These results suggest that the signalling pathway mediated through Rho kinase may have an important role in bronchial smooth muscle tone in allergen induced and virus induced AHR and should be considered as a novel target for asthma treatment.